Mechanical and structural properties of the butt welded joint in high strength structural steel (ST52-3) using gas metal arc welding and oxyfuel gas welding - Ariff, Tasnim Firdaus; Al-Qwairi, Osamah Omar (The Mattingley Publishing Co., Inc., 2020)
High strength structural steel plates (ST52-3) can be welded by many types of fusion welding processes. While each type of fusion welding process has its own advantages and disadvantages, direct comparison on the types of fusion welding processes on the mechanical and structural properties are not clearly seen. Therefore, this article focuses on the effects of Gas Metal Arc Welding (GMAW) and Oxyfuel Gas Welding (OFW) on the mechanical and micro structural properties in butt welded high strength structural steel plates (ST52-3). Hardness, tensile, impact and bending strength were investigated while for micro structural properties, Scanning Electron Microscope (SEM) was used. Overall improved mechanical properties were found at the butt welded joint from using GMAW. There is an increase in hardness (3.6%), tensile strength (32%), impact strength (13.7%) and bend strength (300%). SEM images showed that more uniform and smaller sized needle like structures of acicular ferrite were present at the joint surface of the GMAW samples which contributed to the improved mechanical properties. OFW on the other hand, had some porosities and the effect of heat affected zone on the sample lead to lower mechanical properties with the presence of coarser grain structure. GMAW is a better option than OFW in welding ST52-3 steel plates since the former has shown overall improved properties.